Evaluation of the degree of clinical rheumatoid arthritis activity based on the concentrations of cytokines TNF-alpha, IL-12, IL-15, and IL-18 in serum and synovial fluid - Petrović-Rackov Ljiljana (Vojnosanitetski Pregled)
Bacground/Aim. Experimental in vitro and in vivo investigations in a mouse model have proved that TNF-alpha, IL-12, IL- 15 and IL-18 participate in the pathogenesis of erosive inflammatory arthritis. The aim of this research was to determine the clinical significance of cytokines in the evaluation of the activity of rheumatoid arthritis (RA). Methods. Inside a 4-year period we followed-up 64 patients with RA as newly occurred or in the phase of worsening. We observed the clinical manifestation of the disease upon wluch we divided the patients in to 3 groups: the patients with low active RA, patients with moderate active RA, and the patients with wild active RA. The control group (n = 25 patients) included the patients with osteoarthrosis (OA), and arthritis of the knee. In the samples of serum of all of the patients the concentrating of cytokines TNF-alpha, IL-12, IL-15, and IL-18 were determined using the immunoenzymatic methods in mice for human interleukines. By comparing the concentrations in 30 patients with the high, 14 patients with moderate, and 20 patients with the mild activity of RA it was determined that the patients with the high degree of the disease activity, had significantly high (p < 0.01; p < 0.05) concentrations of the examined cytokines in blood and synovial fluid as compared to the patients with the moderate and mild active disease. There was a relationship (p < 0.01) between the concentrations of cytokines in blood and synovial fluid with the quantity of the Disease Activity Score in 28 joints. Conclusions. Cytokines concentrations could be good indicators of the degree of the general activity of RA. This research could contribute to the interpretation of insufficiently well known views of the pathogenesis role and significance of citokines in an active disease.